Legal Certainty Regarding the Merger of the Population and Civil Registration Services of North Sumatra Province - Munthe, Gerald Elisha (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
Bureaucratic reform in Indonesia is an act of innovation that includes restructuring, rehabilitation, and refunctionalization. This article aims to evaluate the procedures for merging the Population and Civil Registration Service with other agencies by applicable legal regulations. The focus of this research is to determine whether the merger process complies with the hierarchy of statutory regulations. The research method used is a normative juridical research method, which involves the analysis of legal rules and a conceptual approach. Data was collected through document studies and literature references related to primary, secondary, and tertiary law. The results of this study conclude that the process of merging the Regional Apparatus Organizations (OPD) of the Population and Civil Registration Service does not ensure compliance with the hierarchy of statutory regulations, and this action can be considered a violation committed by the provincial government because it was carried out inappropriately both substantively and formally.